Earthquakes time series visualization in cilacap earthquake zone using QGIS and USGS data sets - Ninik Agustin; Nani Kurniasih; Mochamad Taufiqurrochman Abdul Aziz Zein (LPPMPK- Universitas Muhammadiyah Cileungsi, 2023)
Cilacap region earthquakes often occur with more than 5 Richter Scale. With these seismic conditions, earthquake studies in the Cilacap region will always be needed. These studies usually only have output in form of map visualization spatially, however, they have not been compiled in a time series. This study attempts to include visualization of spatial data in the form of a time-series. The data visualization was presented in form of graphs and maps. Graphical visualization using line bar graph type by applying descriptive statistics tries to determine the earthquake’s magnitude fluctuation. The other visualization in form of Heatmap map analysis applying the Kernel Density method is interpolated earthquake magnitude spatial data. The data used in this research was retrieved from the USGS datasets between 1918 to 2021. The spatial boundaries were taken from -7.324 ˚S, 107.941˚E to -10.407˚S, 111.116˚E. The results of spatial data visualization using the heatmap techniques were then analyzed temporally using the Temporal function in the QGIS software. The results of temporal analysis within a year are then sequenced into a video which is displayed on the following link https://youtu.be/m3B7HkfI8qY. The descriptive statistical analysis shows that Earthquakes have magnitudes ranging from 3.3 to 7.58 with a mean of 4.58 and a mode of 4.4. Heatmap analysis shows the results of earthquake magnitude interpolation with high density, located in the south of Cilacap and south of Yogyakarta. Also, the spatiotemporal analysis results show that there is a change in location trends that have high earthquake magnitude density values